2020
DOI: 10.4314/njpar.v41i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Status of intestinal parasites in inmates of a correctional facility, Jos, Nigeria

Abstract: Correctional inmates are among the vulnerable groups to intestinal parasitic infections due to deprived situations characterized by inadequate  facilities, malnutrition, scarce potable water, over-crowding, and poor hygiene. Two hundred and fifty faeces of inmates of Jos Correctional Facility were investigated for the prevalence of intestinal parasites between May and June 2019, using the wet mount and formol-ether concentration techniques. Results obtained showed that from the 250 faecal samples exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Eight of the studies, 4 among street dwellers [ 25 28 ] and another 4 among prison inmates [ 16 19 ] were conducted in Ethiopia. Two studies conducted among prison inmates were reported from Nigeria [ 13 , 21 ]. Malaysia, Nepal, Brazil, Kenya and India reported one study each on prison inmates [ 14 , 20 , 22 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the studies, 4 among street dwellers [ 25 28 ] and another 4 among prison inmates [ 16 19 ] were conducted in Ethiopia. Two studies conducted among prison inmates were reported from Nigeria [ 13 , 21 ]. Malaysia, Nepal, Brazil, Kenya and India reported one study each on prison inmates [ 14 , 20 , 22 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Street dwellers and prison inmates represent the marginalized communities and the overall low levels of living standards make them prone to parasitic illness than the general population [ 15 ]. The prevalence of intestinal parasitic infection among prison inmates showed 42.6%–72.73% in Ethiopia [ 16 19 ], 24.7% in Kenya [ 20 ], 14.4% and 22.8% in Nigeria [ 13 , 21 ], 6% in Nepal [ 22 ], 7.89% in India [ 23 ], 26.5% in Malaysia [ 14 ] and 20.2% in Brazil [ 24 ]. Whereas, the prevalence of intestinal parasites among street dwellers was reported as 43.9%–89.7% in Ethiopia [ 25 28 ], 66.3% in Peru [ 29 ] and 71.7% in Sudan [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of IPIs among inmates of the three prison studies was 38.2% (95% CI: 33.72%–42.79%). A comparable prevalence of 39.3% has been reported in Cameroon, 12 while lower prevalence of 33.5% has been found in a Guinean Prison, 5 24.7% observed in Kenyan prisons, 4 22.8% among inmates in Jos, Nigeria, 3 26.5% in Malaysian prison, 13 and 6% prevalence in Nepal prison 14 . Conversely, a higher prevalence of 48.1% has been found among Arba Minch inmates in Southern Ethiopia 6 and 48.8% among inmates in Umuahia Abia State in Nigeria 15 …”
Section: Discussionmentioning
confidence: 63%
“…F I G U R E 1 Map of Ghana showing all prisons with arrows pointing to the study sites. Source: https://www.ccmghana.net/index.php/2015-2017/hiv-aids/ppag/the-grant Studies have reported varied prevalences of intestinal parasitic infections among prison inmates in different countries, ranging from 22.8%, 24.7%, and 33.5% in Nigeria, 3 Kenya, 4 and Guinea, 5 respectively and as high as 48.1% among prison inmates in Ethiopia. 6 These startling results coupled with the fact that most of these inmates would be present in the facility for years without adequate medical attention leaves little to be desired.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, detection of intestinal helminths such as hookworms, Strongyloides stercoralis, Trichuris trichiura, Ascaris lumbricoides, Hymenolepis nana, Taenia spp., Enterobius vermicularis or Schistosoma spp. is a common feature [ 5 , 11 , 13 , 15 , 17 , 19 , 20 , 22 24 , 29 ]. In fact, Terefe et al, [ 18 ] reported a prevalence of 47.4% of intestinal helminths among inmates in the Bedele prison in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%